Prevention of Bleomycin-Induced Pulmonary Inflammation and Fibrosis in Mice by Paeonol - Liu, Meng-Han; Lin, An-Hsuan; Ko, Hsin-Kuo; Perng, Diahn-Warng; Lee, Tzong-Shyuan; Kou, Yu Ru (Frontiers in Physiology, 2017)
Pulmonary fibrosis is a severe and progressive disease that is characterized by an abnormal deposition of extracellular matrix, such as collagens. The pathogenesis of this disease may be initiated by oxidative damage of lung epithelial cells by fibrogenic stimuli, leading to lung inflammation, which in turn promotes various lung fibrotic responses. The profibrogenic effect of transforming growth factor-beta1 (TGF-beta1) on lung fibroblasts is crucial for the pathogenesis of this disease. Paeonol, the main phenolic compound present in the Chinese herb Paeonia suffruticosa, has antioxidant and anti-inflammatory properties. However, whether paeonol has therapeutic effects against pulmonary fibrosis remains unclear. Using a murine model, we showed that 21 days after the insult, intratracheal bleomycin caused pulmonary inflammation and fibrosis, as evidenced by lung histopathological manifestations and increase in various indices. The inflammatory indices included an increase in total cell count, differential cell count, and total protein concentration in bronchoalveolar lavage fluid. The fibrotic indices included an increase in lung levels of TGF-beta1, total collagen, type 1alpha1 collagen (COL1A1), and alpha-smooth muscle actin (alpha-SMA; a marker of myofibroblasts). Bleomycin also was found to cause an increase in oxidative stress as reflected by increased levels of malondialdehyde and 4-hydroxynonenal in the lungs. Importantly, all these pathophysiological events were suppressed by daily treatment with paeonol. Using human lung fibroblasts, we further demonstrated that exposure of human lung fibroblasts to TGF-beta1 increased productions of alpha-SMA and COL1A1, both of which were inhibited by inhibitors of Jun N-terminal kinase (JNK), p38, and Smad3. JNK and p38 are two subfamily members of mitogen-activated protein kinases (MAPKs), whereas Smad3 is a transcription factor. TGF-beta1 exposure also increased the phosphorylation of JNK, p38, and Smad3 prior to the induction of alpha-SMA and COL1A1. Notably, all these TGF-beta1-induced cellular events were suppressed by paeonol treatment. Our findings suggest that paeonol has antioxidant, anti-inflammatory, and anti-fibrotic functions against bleomycin-induced pulmonary fibrosis in mice. The beneficial effect of paeonol may be, at least in part, mediated through the inhibition of the MAPKs/Smad3 signaling.